The habitual use of plant alkaloids and the prevalence of myocardial diseases. - Saeed, Basil N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The plant (Khat) contains at least 40 types of alkaloids. It has an adrenergic like effect especially on the heart one of these alkaloid is cathedulins group which has molecular height of 600- 1200mm.I/L. it is used frequently mainly at the African horn region (e.g. yemen). This plant alkaloids used by people in form of bands (each band is about 50gm, two bands 100gm and so on). Patients and methods: Three groups of Patients have been included in this study. Group A: (30) patients with dilated cardiomyopathy, Group B: (50) patients with history of ischemic heart disease with clinical presentation of ischemic cardiomyopathy and Group C: (80) cases (50 cases of ischemic cardiomyopathy, 30 cases dilated cardiomyopathy). Used as control group to see the difference from stopping the Khat without adding any medication during the follow up peroid this was over a year with monthly checkup. The place of this was Yemen-Sannaa general hospital and Sannaa private international clinic. Results: This study showed that the age range of patients and volunteers was similar, mean age (35- 65 years), all were male because this plant is used by most of the males and there was difficulty in discussing this problem with the female these three groups were categorized into two groups according to the amounts of all khat bands consumed. Group1: people using about 50gm of this plant and did comprise 75% of all the cases. Group2: people using about 50-150gm of this plant and comprising 25% of all the cases. This study did not show any significant correlation between the incidence of dilated cardiomyopathy and the chronic use of this plant alkaoild, also there was no correlation between the duration of using this alkaloid and probability of getting these cardiac disorders. Stopping consuming this alkaloid did not change the clinical feature dramatically except reduction of liver enzymes elevation. Conclusion: No significant correlation between using the plant khat and development of ischemic and non ischemic dilated cardiomyopathy.